2008
DOI: 10.1001/archinternmed.2007.10
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Antiretroviral Treatment in a South African Program<subtitle>A Cohort Study</subtitle>

Abstract: HAART provided through these South African government health services seems as effective as that provided in high-income countries. Delays starting HAART contributed to high mortality rates. Faster expansion and timely commencement of HAART are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
143
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(154 citation statements)
references
References 15 publications
10
143
0
1
Order By: Relevance
“…Of the nine, seven reported an estimate for the effect of cotrimoxazole on mortality, [28][29][30][31][32][33][34] whereas three reported an estimate for the effect on morbidity. 28,35,36 Two studies also reported the preventive effect on malaria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the nine, seven reported an estimate for the effect of cotrimoxazole on mortality, [28][29][30][31][32][33][34] whereas three reported an estimate for the effect on morbidity. 28,35,36 Two studies also reported the preventive effect on malaria.…”
Section: Resultsmentioning
confidence: 99%
“…28,35,36 Two studies also reported the preventive effect on malaria. 28,36 Assessment of publication bias indicated that three studies [28][29][30] were of high methodological quality, while the other six [31][32][33][34][35][36] were of moderate methodological quality (Table 4, available at: http://www.who. int/bulletin/volumes/90/2/11-093260).…”
Section: Resultsmentioning
confidence: 99%
“…Our prevalence is similar to recent data from Western Cape (32%), 12 but higher than generally reported among ART-eligible adults in Africa (3%-19%). 10,11,16,[18][19][20] This reflects systematic screening of our patients using multiple modalities, and a broad case definition allowing diagnosis based on radiological and clinical features highlighting the 'real life' burden, and recognising that sputum culture misses some cases of disseminated tuberculosis. 21 Our 18% prevalence of cultureconfirmed pulmonary tuberculosis accords with studies from Cambodia (17%), 22 KwaZulu-Natal (19%), 16 and Western Cape (17%).…”
Section: Discussionmentioning
confidence: 99%
“…Outcome data have been available from selected sites, either individually [62,63] or as part of collaborative analyses [65,118], substantiating the perceived clinical benefits of treatment, while at the same time demonstrating how scale-up resulted in inevitable difficulties to retain or confirm that patients were in care. Outcomes from routine government reporting were initially only available from monitoring systems in the Western Cape and Free State Provinces, based on a mix of paper-based systems and electronic capture [119,120]. The adaptation of the routine paper-based cohort monitoring later evolved into a flexible three-tier system comprising paper-based, electronic register and full electronic medical record systems.…”
Section: Programme Monitoringmentioning
confidence: 99%